Extracellular Fluid Volume Is an Independent Determinant of Uncontrolled and Resistant Hypertension in Chronic Kidney Disease: A NephroTest Cohort Study. Issue 19 (2nd October 2018) - Vidal‐Petiot, Emmanuelle; Metzger, Marie; Faucon, Anne‐Laure; Boffa, Jean‐Jacques; Haymann, Jean‐Philippe; Thervet, Eric; Houillier, Pascal; Geri, Guillaume; Stengel, Bénédicte; Vrtovsnik, François; Flamant, Martin
Abstract : Background: Hypertension is highly prevalent during chronic kidney disease (CKD) and, in turn, worsens CKD prognosis. We aimed to describe the determinants of uncontrolled and resistant hypertension during CKD. Methods and Results: We analyzed baseline data from patients with CKD stage 1 to 5 (NephroTest cohort) who underwent thorough renal explorations, including measurements of glomerular filtration rate (clearance of 51 Cr‐EDTA) and of extracellular water (volume of distribution of the tracer). Hypertension was defined as blood pressure (BP; average of 3 office measurements) ≥140/90 mm Hg or the use of antihypertensive drugs. In 2015 patients (mean age, 58.7±15.3 years; 67% men; mean glomerular filtration rate, 42±15 mL/min per 1.73 m 2 ), prevalence of hypertension was 88%. Among hypertensive patients, 44% and 32% had uncontrolled (≥140/90 mm Hg) and resistant (uncontrolled BP despite 3 drugs, including a diuretic, or ≥4 drugs, including a diuretic, regardless of BP level) hypertension, respectively. In multivariable analysis, extracellular water, older age, higher albuminuria, diabetic nephropathy, and the absence of aldosterone blockers were independently associated with uncontrolled BP. Extracellular water, older age, lower glomerular filtration rate, higher albuminuria and body mass index, male sex, African origin, diabetes mellitus, and diabetic and glomerular nephropathies were associated with resistant hypertension. Conclusions: In this large population of patients with CKD, a lower glomerular filtration rate, a higher body mass index, diabetic status, and African origin were associated with hypertension severity but not with BP control. Higher extracellular water, older age, and higher albuminuria were independent determinants of both resistant and uncontrolled hypertension during CKD. Our results advocate for the large use of diuretics in this population.